Our encounters with evil : adventures of Professor J.T. Meinhardt and his assistant Mr. Knox - Mignola, Mike; Mignola, Mike (Dark Horse Books, 2019)
"Backed by the dauntless vampire hunter Ms. Mary Van Sloan, the heroes of Mr. Higgins Comes Home pursue vampires, werewolves, and other horrors that even they are hard-put to name or explain. The only thing that's for certain is that the strange truths these adventurers uncover are seldom what they seem"--